2013
DOI: 10.1166/jnn.2013.7496
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanostructures on Polyethylene Terephthalate Substrate by Interference Lithography and Plasma Etching

Abstract: We report results of an attempt to create nanostructures on polyethylene terephthalate substrate using the interference lithography and plasma etching technique. Methods to create nanogrooves, nanopillars, nanofins and nanoholes have been presented. The effects of chemical and physical etching associated with plasma etching on the synthesis of nanostructures were examined in detail. Different etch rates and anisotropy as a function of plasma power and pressure were reported and explained, offering good underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A layer of photoresist (Ultra-i 123) was then spin-coated on it at 800 rpm for 150 s, and soft-baked at 90°C for 90 s [3]. The micron-size patterns were defined using optical lithography while sub-micron dots and holes were patterned using Lloyd's Mirror interference lithography (LIL) system [28,29]. After exposure, the sample was developed in Microposit MF CD-26 developer for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A layer of photoresist (Ultra-i 123) was then spin-coated on it at 800 rpm for 150 s, and soft-baked at 90°C for 90 s [3]. The micron-size patterns were defined using optical lithography while sub-micron dots and holes were patterned using Lloyd's Mirror interference lithography (LIL) system [28,29]. After exposure, the sample was developed in Microposit MF CD-26 developer for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The PET sample was placed on the cathode and was thus subject to both ion bombardment and chemical etching. A detailed study of the plasma etching mechanism and how the plasma condition relates to etching profile of the PET substrate has been done and reported previously [29]. It has been shown that as the power of oxygen plasma increases, more oxygen gets ionized in the chamber; the ions are more energetic and both lateral and vertical etch rate of the PET substrate increase.…”
Section: Methodsmentioning
confidence: 99%
“…There are two types of substrates used in this work, 1 mm-thick quartz and 100 μm-thick polyethylene terephthalate (PET). The process was almost the same for both substrates except the use of photoresist; AZ1512 was used for quartz and ultra-i 123 was used for PET [34,35]. The fabrication starts with spincoating the respective photoresist on the substrate, at 2000 rpm for 1 min for AZ1512 and 800 rpm for 2.5 min for ultra-i 123 (step 1).…”
Section: Simulation Development and Experimental Detailsmentioning
confidence: 99%
“…We have attempted to fabricate polymer based nanostructures using the interference lithography (IL) and plasma etching technique for biomedical research due to their potentials in biocompatibility and lower material cost. 21 22 We have also studied in detailed the plasma etching mechanisms 23 In this paper, we report the fabrication and characterization of the Co/Pd films and nanodisc arrays on PET substrate. The flexibility of the PET substrate offers the attractive potential for the fabrication of flexible magnetic devices.…”
Section: Introductionmentioning
confidence: 99%